2011
DOI: 10.1007/s11596-011-0582-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic acetylcholine receptor subtype expression in type vestibular hair cells of guinea pigs

Abstract: Recent studies have demonstrated that five subtypes (M1-M5) of muscarinic acetylcholine receptor (mAChR) are expressed in the vestibular periphery. However, the exact cellular location of the mAChRs is not clear. In this study, we investigated whether there is the expression of M1-M5 muscarinic receptor mRNA in isolated type II vestibular hair cells of guinea pig by using single-cell RT-PCR. In vestibular end-organ, cDNA of the expected size was obtained by RT-PCR. Moreover, mRNA was identified by RT-PCR from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is unclear where these putaLve M5mAChRs reside. Given its slower kineLcs and no obvious interacLons with the tradiLonal EVS-mediated slow excitaLon, it may not be expressed in afferents but in hair cells instead where changes in transmifer release could enhance excitability of the afferent (Derbenev et al, 2005;Holt et al, 2003;Li & Correia, 2011;Yao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear where these putaLve M5mAChRs reside. Given its slower kineLcs and no obvious interacLons with the tradiLonal EVS-mediated slow excitaLon, it may not be expressed in afferents but in hair cells instead where changes in transmifer release could enhance excitability of the afferent (Derbenev et al, 2005;Holt et al, 2003;Li & Correia, 2011;Yao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that all mulLple mAChR subtypes are present in the vesLbular end organs of guinea pigs, rat, and humans (Ishiyama et al, 1997;Li et al, 2007;Yao et al, 2011;Wackym et al, 1996). Thus far, pharmacological data and the presence of EVS-mediated slow excitaLon in M2/M4 double-KO mice suggest that M2 and M4mAChRs are not involved, while other pharmacological data implicate a major role for M3mAChRs and perhaps a minor role for M1mAChRs.…”
Section: Ac-va-on Of M5machrs Enhance the Background Firing Rate Of A...mentioning
confidence: 97%
“…The activation of mAChRs typically leads to downstream events with much slower kinetics than those occurring through nAChR activation. Based on singlecell RT-PCR studies, it was reported that mAChR subtypes M1-5 were all expressed in type II hair vestibular hair cells of the guinea pig (Yao et al 2011) and bird (Li et al 2007). However, only M1, M2, and M5 mAChRs have been detected in the human vestibular periphery (Wackym et al 1996).…”
Section: Muscarinic Acetylcholine Receptorsmentioning
confidence: 99%
“…Besides, m1, m2, m5mAChR subtypes have also been observed in human vestibular periphery by reverse transcription polymerase chain reaction (RT-PCR) studies [10,11]. Recently, immunohistochemical studies have further supported that m1-m5 mAChR subtypes were located in isolated VHCs II of pigeons [12], and RT-PCR has also provided strong evidence that m1-m5 mAChR subtypes were detected in isolated VHCs II of guinea pig [13]. …”
Section: Introductionmentioning
confidence: 99%